Peran pemasaran media sosial dan citra merek terhadap minat beli - Jasmine Jasmine; Chandra Kuswoyo (Universitas Kristen Maranatha, 2025)
Social media-based marketing serves as an instrument that continues to evolve in supporting transactional activities in the modern era, while brand image reflects a perception shaped by past experiences and acquired information. Alongside the rapid growth of e-commerce systems, various online marketplace applications such as Shopee, Lazada, Tokopedia, Bukalapak, and Blibli have become increasingly popular among the public. The purpose of this study is to examine the influence of social media marketing and brand image on purchase intentions, using a sample of 100 respondents selected through purposive sampling. Data was analyzed using multiple linear regression, revealing that social media marketing and brand image collectively contributed 53.9% to purchase intention, whereas the remaining 46.1% was explained by other variables not included in this study.